Effect of remimazolam besylate versus midazolam on time to extubation in critically ill, mechanically ventilated patients: a randomized controlled trial - Renhuai Liu; Binxiao Su; Guifen Gan; Guangming Wang; Chengli Wang; Ning Xu; Guangcai Feng; Hao Guo; Qingxia Yuan; Aiguang Li; Wenping Zheng; Jiang Li; et al. (Frontiers in Medicine)
BackgroundPrevious studies have indicated that the administration of short-acting sedatives prior to weaning from mechanical ventilation is linked to a more rapid recovery and extubation process, in addition to lowering intensive care unit (ICU) treatment expenses. The present study aimed to evaluate the efficacy and safety of the sequential administration of remimazolam besylate compared with midazolam before weaning from mechanical ventilation.MethodsThis multicenter, randomized controlled trial was conducted across medical and surgical ICUs within a tertiary, academic medical center. The study population consisted of critically ill, mechanically ventilated adult patients. Candidates anticipated to be ready for ventilator weaning within 12 h underwent a Spontaneous Breathing Trial (SBT) safety screen. Only those who successfully passed this assessment were considered for inclusion in the final phase of the study and subsequent randomization. The patients were randomized into two groups: group M, in which the sedative regimen was transitioned to midazolam, and group R, which involved a switch to remimazolam. Sedative dosages were titrated to achieve a target Richmond Agitation-Sedation Scale (RASS) score between −3 and 0. The primary endpoint of this study was the time to extubation.ResultsA total of 435 patients underwent screening, of whom 306 patients being randomized, and 272 patients ultimately included in the analysis, comprising 132 patients in group M and 140 patients in group R. The patients in group R maintained lighter levels of sedation compared to those in group M. The patients in group R showed significantly earlier recovery (p < 0.05) and extubation (p < 0.05) at the same RASS score prior to the cessation of sedatives. Higher prevalence of agitation was observed in group M as opposed to group R (20.45% versus 8.57%, p = 0.005). However, no significant difference in the incidence of delirium was noted between the groups.ConclusionIn critically ill, mechanically ventilated patients, the use of remimazolam besylate was associated with a shorter time to recovery and extubation prior to ventilator weaning, along with a lower incidence of agitation.Clinical trial registrationIdentifier ChiCTR 2200065048, https://www.chictr.org.cn.